Um registro sobre as transformações e tenacidades na paisagem urbana: o caso da rua Pouso Alegre – Belo Horizonte - Camila Kelly Carneiro (2017)
The present work examines the transformations and urban uses in Pouso Alegre street in the neighborhood Floresta, related to the existing interfaces between the Land Use and Land Use Law, the historical cultural heritage policies, and the ways in which they are appropriated by the population that lives with these spaces transformed into patrimony of the city. It can be noticed that, over a few decades, Pouso Alegre Street in the stretch that includes the Lagoinha tunnel to Flávio dos Santos Street, especially in the area that communicates with the city center, had great social and urban importance, polarizing and responding to the process of urbanization that the city of Belo Horizonte as a whole faced. Of course, these transformations always consist of processes of short or long duration, starting from initial, original states, to other situations that, even planned and circumscribed, can have consequences of difficult measurement. In this way of analysis, the transformations provoked by the action of man, which aim to adapt the growth of the city to the needs of the population, can be considered as intermediate states, species of hiatus where it is possible to locate, visually, different circumstances between the urban uses. On the other hand, there are the tenacities, that is, the buildings that persist while maintaining their original characteristics, although they have marks of the inevitable action of time, much subtler. In this sense, aiming at a better understanding of the dynamics of growth, analyzes of the Pouso Alegre street landscape were performed through the processes of ruptures, continuities and overlaps involved in the transformation process.